Application of Swertia Chirayita (Roxb. ex Fleming) Karst in Wheat Flour to Design Health Food - Subedi, Ishwar; Karki, Tika Bahadur (Journal of Food Science and Technology Nepal, 2018)
Swertia Chirayita often known as Chiraito is a highly traded medicinal plant of Nepal. Its use in food industries is still under research. Application of the medicinal herb in bread prepared from wheat flour (550 types, 431 µm particle sized with moisture 12.5%) was assessed to evaluate sensory and physiochemical qualities. The antioxidant activity of the Chiraito was found to be 62% at 500 μg/ml and 15% at 100 μg/ml by radical scavenging method which shows Chiraito as the most significant antioxidants potential. Likewise, antibacterial activity of the herb extract also showed significantly inhibitory to selected pathogenic microorganism. Finding its functional properties, Chiraito powder (669 µm particle sized) with 1.0 %, 0.10%, 0.00% and 0.01% respectively were added in wheat flour to make four different type of bread and carried out sensory evaluation using 9-points (Hedonic Rating Test). The data were statistically analyzed using SPSS for Analysis of Variance (ANOVA) at 5% level of significance. The overall quality of the finished products also showed that Chiraito, as herb extract didn’t affect physico-chemical properties of the product which was measured in terms of dough yield, bread volume, elasticity, acid degree, water content, crumb porosity, texture, smell and taste. Overall acceptability showed that bread (Sample D) with 0.010% was superior and liked the most. Since no entrance of Chiraito herb in modern food industries yet, the research would support production and commercialization of innovative functional health food globally.